Self-efficacy as mediator in relationship between transformational leadership and organizational commitment among secondary school teachers in central region, Peninsular Malaysia - Teh, Pei Ling (2016)
Malaysian schools are experiencing constant educational challenges in the current 21st century teaching and learning, this scenario requires greater teacher’s organizational commitment in accomplishing effective learning outcomes. Teachers are the agents of change in carrying out education plans and changes in schools to the benefits of the nation. School teachers get directive instructions from the principals to transform current education system. Hence, to what extent do the secondary school teachers fare in their organizational commitment? The aim of this study is to examine the mediation effect of teacher’s self-efficacy in the relationship between principals’ transformational leadership practices and teachers’ organisational commitment. It was a descriptive correlational study using a survey method. Proportionate stratified random sampling was used for the selection of respondents. 349 secondary school teachers in the central region of Peninsular Malaysia were involved in a cross-sectional survey. The number of respondents was determined by Krejcie and Morgan (1970). The response rate stood at 86.9%. The reliability and validity of the research questionnaires were determined using coefficient alpha and composite reliability for the subsequent descriptive analysis, correlation analysis, and confirmatory factor analyses. The statistical procedures used to analyse the data for addressing the research questions and hypotheses included descriptive, Structural Equation Modelling (SEM) and mediation analysis. Given that the hypothesized model exhibits a good fit to the data, the findings showed a high level of transformational leadership, (M= 4.66, SD = .67, score range from 1 to 6) and a high level of teachers’ organizational commitment, (M = 3.82, SD = .48, score range from 1 to 5). The level of teachers’ self-efficacy was high, (M=3.93, SD= .45, score range from 1 to 5). Furthermore, the correlation between transformational leadership and teachers’ self-efficacy was positive and had a medium strength, (r=.45, p<.01). Teachers’ self-efficacy and organizational commitment revealed a positive and had a medium strength of correlation, (r=.37, p<01). Only transformational leadership and organizational commitment had a positive and strong correlation , (r=.5, p>.01). Specifically, the findings revealed that self-efficacy has a partial mediating effect in the relationship between principals’ transformational leadership practices and teachers’ organizational commitment using bootstrapping method. Teachers’ self-efficacy and transformational leadership only contributed 27.2% towards organizational commitment among the teachers in the secondary schools in the central region of Peninsular Malaysia. The findings revealed teachers’ self-efficacy serves as a partial mediator in the relationship between principals’ transformational leadership practices and organizational commitment. Due to the partial effect as a mediator, there are other factors that could influence Malaysian teachers’ organizational commitment. Future research should investigate more factors that influence teachers’ organizational commitment. The officers in Ministry of Education and the school management should continue the effort in boosting teachers’ self-efficacy in schools by providing more professional training and development. The findings provide an impetus for policies makers and school management to continue adopting effective transformational leadership practices in their schools that will influence higher organizational commitment among the secondary school teachers. All these effort are to move towards implementing change and achieving the 11 shifts in Malaysia Education Blueprint (2013-2025) nationwide.